The future of antimicrobial therapy in the era of antibiotic resistance in cystic fibrosis pulmonary infection. (August 2013) - McCaughey, G; Gilpin, DF; Elborn, JS; Tunney, Michael M
Cystic fibrosis (CF) is characterised by chronic polymicrobial airway infection and inflammation, which is the major cause of morbidity and mortality. Aggressive use of antimicrobials has been fundamental in increasing the life expectancy of CF patients in recent years. However, enhanced culture and non-culture based detection methods have identified bacteria in the CF lung not previously isolated from CF patients by routine diagnostic microbiology Coupled with increasing antimicrobial resistance, the future of antimicrobial therapy in CF respiratory infection remains challenging. New strategies are needed to address these problems and ensure improvements in life expectancy are maintained. Potential future strategies include the use of new antimicrobial agents and formulations currently in clinical trials, alternative methods of selecting appropriate therapeutic regimens, determination of the pathogenicity of species newly associated with CF and the development of new antimicrobials and adjuvants for use in clinical practice.